Poor Prognostic Factors and Associated Outcome in Children Admitted at Tertiary Care Hospital, Hyderabad - Aamir Memon, Abdul Harneed Radhan, Sajjad Ali Kazi , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To evaluate the causes of hospitalization, poor prognostic factors and associated outcome in children admitted at Tertiary Care Hospital, Hyderabad. Methods: A descriptive prospective case series was conducted in the Department of Pediatric, Isra University Hospital, Hyderabad, in the period of twenty three months. A total of 229 children between the ages of 2 years to 17 years of both genders admitted in the Department of Pediatrics Isra University Hospital, due to any underlying cause were enrolled in this study. Children were divided into two age groups; group A (age between 02 years to 09 years) and group B (age between 10 years to 17 years). Their prognosis and outcome was documented. Results were statistically analyzed. Results: Mean age of admitted children was 6.23 + 9.68. The mortality rate by tetanus disease was 12.22% (n = 28 out of total 229 admitted children). Most common cause of admission in group A children was malnutrition (38.51%, n = 57) and in group B children was respiratory tract infection (39.5%, n = 32). Poor outcome was observed more in group A children (7.42% n = 17) as compared to group B children (4.80% n =11). Conclusion: There are different risk factors involved in different age groups which prone them for hospitalization and are also associated with poor outcome mainly malnutrition and respiratory tract infection in 02 to 17 years age groups.